Hemagglutinin homologue from H17N10 bat influenza virus exhibits divergent receptor-binding and pH-dependent fusion activities - Zhu, Xueyong (National Academy of Sciences, 2013)
Bat influenza virus H17N10 represents a distinct lineage of influenza A viruses with gene segments coding for proteins that are homologs of the surface antigens, hemagglutinin (HA) and neuraminidase (NA). Our recent study of the N10 NA homolog revealed an NA-like structure, but with a highly divergent putative active site exhibiting little or no NA activity, and provided strong motivation for performing equivalent structural and functional analyses of the H17 HA protein. The overall structure of the H17 HA homolog from A/little yellow-shouldered bat/Guatemala/060/2010 at 3.18 Å resolution is very similar to other influenza HAs, with a putative receptor-binding site containing some conserved aromatic residues that form the base of the sialic acid binding site. However, the rest of the H17 receptor-binding site differs substantially from the other HA subtypes, including substitution of other conserved residues associated with receptor binding. Significantly, electrostatic potential analyses reveal that this putative receptor-binding site is highly acidic, making it unfavorable to bind any negatively charged sialylated receptors, consistent with the recombinant H17 protein exhibiting no detectable binding to sialylated glycans. Furthermore, the fusion mechanism is also distinct; trypsin digestion with recombinant H17 protein, when exposed to pH 4.0, did not degrade the HA1 and HA2, in contrast to other HAs. These distinct structural features and functional differences suggest that the H17 HA behaves very differently compared with other influenza HAs.